Optimizing Solar Parabolic Concentrators with Cylindrical and Conical Receivers for Improved Thermal Performance - Farhat Mohamad; Mazloum Yousef; Wakim Samer; Nader Wissam Bou; Al-Ebrahim Meshari; Ghareeb Nader (E3S Web of Conferences)
This study investigates the optical and thermal performance of solar parabolic concentrators with cylindrical-conical receivers for low-temperature heat and power generation, emphasizing the effect of receiver geometry on efficiency. It finds that maximum optical efficiency occurs when the receiver aperture aligns with the focal point, providing greater stability and less sunray leakage. The study also highlights how cone angles, receiver aspect ratio, and precise positioning significantly improve efficiency. Sealing the receiver with glass reduces convective losses, increasing thermal efficiency from 40-62% to over 80%. Future work will explore secondary reflector cones and spherical receivers to optimize configurations for decentralized solar systems, showcasing the technology’s potential for efficient solar energy capture and conversion.